Relationship between polycomb‐group protein BMI‐1 and phosphatases regulating AKT phosphorylation level in endometrial cancer. Issue 2 (21st December 2019) - Zaczek, Agnieszka; Jóźwiak, Paweł; Ciesielski, Piotr; Forma, Ewa; Wójcik‐Krowiranda, Katarzyna; Cwonda, Łukasz; Bieńkiewicz, Andrzej; Bryś, Magdalena; Krześlak, Anna
Abstract: The PI3K/AKT pathway is frequently activated in endometrial carcinoma. BMI‐1 (B‐lymphoma Mo‐MLV insertion region 1) protein affects expression of PTEN (phosphatase and tensin homolog) in some cancers, but its significance for endometrial tumorigenesis is not known. The objective of this study was to determine the relationship between BMI‐1 and expression of factors affecting AKT (protein kinase B) phosphorylation level in endometrial cancer. The expression of proteins and mRNAs was investigated in endometrial cancer specimens and samples of non‐neoplastic endometrial tissue by Western blot and RT‐PCR, respectively. The impact of BMI‐1 down‐regulation on AKT phosphorylation and expression of genes coding for several phosphatases were studied in HEC1A cells. The results showed that BMI‐1 depletion caused increase in PHLPP1 and PHLPP2 (PH domain and leucine‐rich repeat protein phosphatases 1/2) expression and decrease in phospho‐AKT (pAKT) level. In more advanced tumours with higher metastatic potential, the expression of BMI‐1 was lower compared to tumours less advanced and without lymph node metastasis. There were significant inverse correlations between BMI‐1 and PHLPPs, especially PHLPP1 in normal endometrial samples. The inverse correlation between BMI‐1 and PHLPP1/PHLPP2 expression was observed in PTEN positive but not PTEN negative cancers. Low PHLPP2 expression in tumours predicted poorer overall survival. BMI‐1 impacts on AKT phosphorylation level in endometrial cells by regulation of PHLPP expression.